Leaching behavior of germanium from germanium-rich lignite: A further comprehension of its occurrence state - Zhiyuan Zhang; Yanyan Xu; Guixia Fan; Yingrui Jin; Daoguang Teng; Guosheng Li; Peng Li; Yijun Cao (Fuel Processing Technology)
Germanium, a critical metal used in many strategy fields, is widely acknowledged as organic affinity. Germanium is main occurred in the humus of lignite, but its exact occurrence state remains unclear. In this work, various methods were employed to leach germanium from lignite to reveal the germanium occurrence state. Germanium tends to accumulate in specific germanium-endowed structures, but most germanium is bound to and encapsulated in enwrapping structures such as humic acid. It could be extracted either by co-extraction with humic acid (e.g. ammonoxidation, alkaline leaching) or by dissociating the germanium-endowed structure (e.g. thionyl chloride leaching, acid demineralization, and hydrochloric acid leaching). In germanium-rich lignite, germanium was directly connected to oxygen and chelated by the phenolic hydroxyl in the ortho- in the form of a five-membered ring. Furthermore, germanium existed in the germanium-endowed structure in the form of a six-coordinated, deformed octahedron, externally encapsulated by interfering substances. Therefore, this study provides a theoretical basis for targeted extraction of germanium from germanium-rich lignite.